The role and importance of environmental education in the system of environmental law and order (Journal of actual problems of jurisprudence, 2023)
To date, the unfavorable environmental situation remains one of the acute problems in the Republic of Kazakhstan. According to certain experts of this industry, the ecological situation and the state of the environment in Kazakhstan and the CIS countries is among the worst in the world. In this article, a comprehensive legal analysis of environmental education and upbringing in the Republic of Kazakhstan is carried out, the legal foundations of provision and implementation are considered. The formation of legal regulation of environmental education and upbringing in accordance with the norms of national law has been studied. The proposals and theoretical issues aimed at forming an understanding of ecological and legal consciousness as the main factor contributing to the solution of environmental problems are considered. As a result of a comparative study of the environmental legislation of the Republic of Kazakhstan, including on issues of environmental education and education, enlightenment and culture, proposals for the allocation of effective perspective norms, as well as their implementation in the norms of national legislation, were considered. This study was prepared as part of the implementation of the grant funding research project by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan (Grant No. AP14872548 Modern environmental Law and order: Kazakhstan case). Key words ecological danger, ecological education, ecological and legal consciousness, ecological education and upbringing, environmental legislation.